Electrochemical-energy- exergy analysis of reversible solid oxide cell-based small-scale stand-alone energy storage system - Agbaje, Muiz Adekunle; Akkaya, Ali Volkan (ELSEVIER, 2023)
The present renewable energy systems should shift towards more storage-based systems due to their inherent intermittency. This study examines the electrochemical, energy, and exergy performances of a Reversible Solid Oxide Cell (ReSOC) based stand-alone energy storage system with a pressurized gas tank. The system operates in the fuel cell mode (SOFC) for power generation and electrolysis cell mode (SOEC) for syngas production. The exergy analysis gives a detailed insight into the irreversibility points in both system operation modes. The ReSOC system model is based on a validated ReSOC stack electrochemical model and system components' massenergy balance model. The power extraction level in the ReSOC stack was shown to determine the thermal management required through the electrochemical analysis. The energy analysis resulted in a system roundtrip efficiency of 51 % at the considered operating conditions. In addition, the highest points of exergy loss/destruction are the exhaust air (SOFC: 32 %, SOEC: 34 %), ReSOC stack (SOFC: 25 %, SOEC: 28 %), and pressure regulation valve (SOFC: 11 %, SOEC: 17 %). The results also show that the SOEC mode performed better than the SOFC mode in the energy and exergy analyses. This study may be used as a basis for stand-alone system performance improvement leading to higher efficiency.
Keywords: Electrochemical analysis; Energy storage; Exergy; Reversible solid oxide cell; Thermoneutral voltage; FUEL-CELL; PERFORMANCE ANALYSIS; INTEGRATION; DESIGN; POWER; MODEL; Thermodynamics